2020
DOI: 10.1016/j.celrep.2020.01.107
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Rational Design of Single-Domain Antibody-Based Antitoxins against Botulinum Neurotoxins

Abstract: Highlights d Crystal structures of six VHHs that bind and neutralize BoNT/ A1 or BoNT/B1 d Three VHHs inhibit the membrane insertion or the light chain unfolding of BoNT/A1 d Three VHHs block the synaptotagmin, ganglioside, and/or lipid binding of BoNT/B1 d Rationally designed bifunctional VHH heterodimers show superior antitoxin potency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 65 publications
4
60
0
Order By: Relevance
“…Previous studies have demonstrated that expression of VHH heterodimeric VNAs composed of two BoNT-neutralizing VHHs can radically improve in vivo antitoxin potencies [ 21 , 25 ]. To similarly increase the potency of BoNT/E VHHs, we initially engineered and produced VHH heterodimer VNAs using the three BoNT/E-neutralizing VHHs identified in the first screen: JLE-E5, JLE-E9 and JLE-G6.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that expression of VHH heterodimeric VNAs composed of two BoNT-neutralizing VHHs can radically improve in vivo antitoxin potencies [ 21 , 25 ]. To similarly increase the potency of BoNT/E VHHs, we initially engineered and produced VHH heterodimer VNAs using the three BoNT/E-neutralizing VHHs identified in the first screen: JLE-E5, JLE-E9 and JLE-G6.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the precise binding sites for JLE-E5 and JLE-E9, which bind to closely apposed epitopes on BoNT/E [ 28 ], we engineered a VNA called JLE-E9/40/JLE-E5 which was predicted to have the optimal VHH orientation and spacer length to facilitate the ability of both VHH components to bind simultaneously to their BoNT/E epitopes ( Figure 4 A,B). To test for simultaneous binding, we performed gel filtration studies ( Figure 4 C) as previously reported [ 25 ]. Co-incubation of JLE-E9/40/JLE-E5 or JLE-E5/29/JLE-E9 with a two-fold molar excess of BoNT/E produced a single peak upon gel filtration, representing the heterodimeric BoNT/E-VNA complex expected when both VHHs are bound to the same molecule ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations